Service product development for Yudharta Advertising and Press - M. Imron Mas'ud; Fiisatir Rodliyah; Ach. Denny Hermawan; Panca Ageng Wibisono; Shidqi Saifuddin Hamzah; Moh. Nur Indra Wahyudi; Wahyu Khoiriyah; M. Athoilah (Universitas Muhammadiyah Magelang, 2023)
Yudharta Advertising and Press is a productive business unit under the auspices of Yudharta Pasuruan University which is engaged in serving book publishing and printing for the general public. This existence aims to help the community in increasing book literacy. The purpose of this service is to increase service products in the productive business unit Yudharta Advertising and Press. Development activities are carried out with FGDs, creating websites, and developing partnerships. The result of this activity is that partners have increasingly varied service products and can be accessed easily by the wider community for their services to be utilized.